Volumetric incentive spirometer and positive pressure after cardiac surgery - Azambuja, Aline C. M; Souza, Milene A; Ranzoni, Eduarda P; Wioppiold, Juliana S; Muzykant, Lizia Marcela P; Costa, Pricila O; Trevisan, Cristiane B.E; Santos, Laura J (Journal of Respiratory and CardioVascular Physical Therapy, 2016)
<p class="MsoNormal" style="margin-bottom: 0.0001pt; text-align: justify; line-height: 150%; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial;">Background:Most patients that undergo cardiac surgery develop post-operative pulmonary complications. The use of an incentive spirometer associated withpositive end-expiratory pressure (PEEP) and non-invasive ventilation (NIV) may contribute to the reduction of such complications. <p class="MsoNormal" style="margin-bottom: 0.0001pt; text-align: justify; line-height: 150%; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial;">Objective: To compare the efficacy of an incentive spirometer associated with positive end-expiratory pressure to NIV in pulmonary complications in the PO of heart surgery during hospitalization in the intensive care unit (ICU). <p class="MsoNormal" style="margin-bottom: 0.0001pt; text-align: justify; line-height: 150%; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial;">Methods: A randomized clinical trial conducted <span style="font-size: 12.0pt; line-height: 150%; font-family: 'Cambria','serif'; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: PT-BR;" lang="EN-US">from July 2012 to July 2015 at the ULBRA Mãe de Deus University Hospital -Canoas/RS. Patients were randomized into three groups: Group I – NIV; group II - <span style="font-size: 12.0pt; line-height: 150%; font-family: 'Cambria','serif'; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Courier New'; color: #212121; mso-ansi-language: EN; mso-fareast-language: PT-BR;" lang="EN">volumetricincentive spirometer (IS) associated <span style="font-size: 12.0pt; line-height: 150%; font-family: 'Cambria','serif'; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: PT-BR;" lang="EN-US">with positive end-expiratory pressure (PEEP) (IS+EPAP); and group III - conventional (CG). The three groups received motor physiotherapy. Post-operative monitoring of pulmonary complications was performed through radiology service reports until the time of discharge from the ICU. <p class="MsoNormal" style="margin-bottom: 0.0001pt; text-align: justify; line-height: 150%; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial;"><span style="font-size: 12.0pt; line-height: 150%; font-family: 'Cambria','serif'; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: PT-BR;" lang="EN-US">Results: 49 patients were included in the study, 13 patients in Group I, 16 patients in Group II and 20 patients in Group III. The average age of Group I was 61.7 ± 10.4 years, 61.4 ± 10.2 years in Group II, and 62.9 ± 11.5 years in Group III. Atelectasis was the pulmonary complication that had the highest statistical significance when comparing the three groups in the immediate PO (p=0.035). <p class="MsoNormal" style="margin-bottom: 0.0001pt; text-align: justify; line-height: 150%; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial;">Conclusion: When comparing non-invasive ventilation (NIV) to incentive spirometry (IS) associated with positive end-expiratory pressure (PEEP) or respiratory exercises, we could not conclude that this particular technique is superior in relation to the decrease of pulmonary complications. <p class="MsoNormal" style="margin-bottom: 0.0001pt; text-align: justify; line-height: 150%; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial;"> <!--[if !supportAnnotations]--> <!--[endif]-->